Management Information System in the Educational Process - Ozioma, CHIGBU Prince; Adamu, AKOR Momoh (Researchparks Publishing, 2023)
The study investigated the role of management information systems in education (MIS) in the normal educational process. The study is library-based, therefore it focused mainly on the review of the key concepts under the following sub-headings: information, information systems, education, information management, and management information systems (MIS). The study also examined the components and resources of the information system and functions of management information systems in education, the role of management information systems in the process of education, and the requirements of management information systems in education. Furthermore, the study looked at the challenges of MIS in education, criteria for effective education management information systems, and the importance of management in the process of education. It also looked at information systems and the issue of manual versus computer-based MIS. The study concluded that MIS is the lifeblood of any educational institution because it’s a process of information sorting, acceptance, storage, utilisation management, and retrieval for the purpose of successful educational administration in any society. Therefore, it was recommended that both public and private schools should be encouraged to be committed to seeking organised information before taking decisions with regards to teaching, learning, and administration. Today’s educational managers should adopt a management information system in education to prevent being outdated with only marginally relevant facts rather than being presented with concrete and absolutely useful information. Finally, all the schools should adopt the computer-based management information system for a more competent academic outcome and to be in line with the world's best educational practices with regards to ICT.